Aspartic acid as a crystal growth catalyst - Piana, Stefano; Jones, Franca; Gale, Julian (The Royal Society of Chemistry, 2007)
Ion desolvation is an important kinetic step in the growth of divalent ionic crystals - a category that encompasses numerous materials relevant to biomineralization. It has recently been shown for one such divalent ionic crystal that the rate-limiting desolvation of the cation can be assisted by the anion and that this process can be surface specific. Here we show that even a simple biological molecule, such as aspartic acid, can have a measurable catalytic effect on barite crystal growth and that this effect is related to the lowering of the activation barrier for cation desolvation. We therefore suggest that growth rate enhancement on specific faces through catalysis of the cation desolvation step may be a viable mechanism for the positive control of biomineralization.